Minority Religions, Religious Freedom, and the New Pan-European Political and Judicial Institutions - Richardson, James T. (A journal of church and state, 1995)
James T. Richardson; Minority Religions, Religious Freedom, and the New Pan-European Political and Judicial Institutions, Journal of Church and State, Volume 37